Evaluation of Posyandu Management in Bogor City - Fitri Amelia; Fasli Jalal; Firman Arifandi (Junior Medical Journal, 2023)
Background: Posyandu is a form of Community-Based Health Efforts (UKBM) carried out by, from and with the community, to empower and provide facilities for the community to obtain health services for mothers, babies and toddlers.  Management of health services is an activity or an art to manage health workers and non-health workers to improve public health through health programs. Maq??id al-Sh?ri' are the purposes desired by the legislator (Allah; al-Sh?ri') by establishing a rule of law. Purpose: The purpose of this study was to determine the posyandu management in Bogor City.Methods: this study used a simple random sampling method, namely by selecting two areas of Bogor City with different levels of urban progress, then proceed with the random selection of sub-districts from each area, then the selection of 10 posyandu and cadres randomly without regard to strata in the population  . Results: From the 10 posyandu samples, the results of the input component were obtained with a value range of 80-95%, the results of the process component with a value of 100%, the results of the output component with a value range of 50-59% and the results of the SKDN indicator 71-94%.Conclusion: Of the ten Posyandu in Bogor City, the Tegallega Sub-District and the Cikaret Sub-district are good Posyandu.